Policy Perspectives on Artificial Intelligence Adoption in Indonesia’s Customs: Feasibility, Barriers, and Implications - Rofiyanti, Eka; Agustina, Dwi; Firzah, Muhammad (Indonesian Association for Public Administration, 2026)
Governments worldwide have adopted Artificial Intelligence (AI) in customs oper ations to enhance efficiency, increase revenue, and improve national security as a fundamental aspect of the country’s vision and mission. However, there is inefficient management and a lack of government commitment to maintaining this consistently. This indicates that global research on AI in customs is abundant, but in developing countries like Indonesia, the priority aspect remains uneven. In addition, this study applies qualitative and content analysis methods to secondary data to test issues in Indonesian customs operations. Essentially, this confirmation indicates that the con cretization of IA in customs operations could enhance administrative processes (e.g., reporting goods, collecting revenue, and reducing goods fraud). These findings un derscore the need for governments to establish regulations and comply with interna tional trade agreements to provide visibility and access to customs operations. In sum mary, this study provides a clear commitment to applying AI in customs operations, with appropriate approaches grounded in visibility and access.